Effect of CeH2.73-CeO2 Composites on the Desorption Properties of Mg2NiH4 - Wu, Kaiyao; Cai, Daqian; Shao, Kaimei; Xue, Tuguang; Zhang, Peng; Li, Wei; Lin, Huai-Jun (Frontiers in Chemistry, 2020)
A series of CeH2.73/CeO2 composites with different ratios of hydride and oxide phases are prepared from the pure cerium hydride via oxidation treatments in the air at room temperature, and they are subsequently doped into Mg2NiH4 by ball milling. The desorption properties of the as-prepared Mg2NiH4+CeH2.73/CeO2 composites are studied by thermogravimetry and differential scanning calorimetery. Microstructures are studied by scanning electron microscopy and transmission electron microscopy, and the phase transitions during dehydrogenation are analyzed through in situ X-ray diffraction. Results show that the initial dehydrogenation temperature and activation energy of Mg2NiH4 are maximally reduced by doping the CeH2.73/CeO2 composite with the same molar ratio of cerium hydride and oxide. In this case, the CeH2.73/CeO2 composite has the largest density of interface among them, and the hydrogen release effect at the interface between cerium hydride and oxide plays an efficient catalytic role in enhancing the hydrogen desorption properties of Mg2NiH4.